Analisis Faktor Yang Mempengaruhi Motivasi Siwa Mengikuti Kegiatan Pramuka Kelas VIII di MTsN 2 Pasaman Barat - Maripa Annisa; Supriadi Supriadi; Nurhasnah Nurhasnah; Jasmienti Jasmienti (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2023)
The factors that influence students' motivation to participate in extracurricular activities are the focus of this study. These factors may originate within the student (internal factors) or from without (external factors). Students' needs, hopes, and interests are all internal factors that can influence their interest in and participation in extracurricular activities. However, external factors include things like family, the natural world, and social equilibrium.This study aims to shed light on the most influential factors influencing grade eight students' decision to participate in extracurricular activities. This study combines descriptive methods with quantitative estimation. Data collection software that makes use of angkets. This study's sample population consists of the sixty-five students that participated in the pre-exam activities at Class VIII of MTsN 2 in Pasaman Barat. This study used a non-probabilistic sampling technique called